ASSESSMENT OF LEAF CHLOROPHYLL CONTENT IN PARTS OF THE THAR DESERT USING REMOTE SENSING TECHNIQUES - SURAJ KUMAR SINGH, JAGPAL SINGH TOMAR, AGNI KUNDU, SUDHANSHU; SRUTI KANGA* (The Journal of Research ANGRAU, 2023)
Recent advances in remote sensing led to an improved approach for monitoring vegetation properties depending on chlorophyll content. The study brings out the importance of indices as valuable approach to measure the chlorophyll content in Luni Upper Basin (Rajasthan and Gujarat). Chlorophyll content was measured using four different vegetation indices, i.e., modified chlorophyll absorption ratio index, chlorophyll index green model, chlorophyll index red-edge model, and normalized differential vegetation index. In addition, the Landsat-8, Operational Land Imager (OLI) for 2015 with spatial resolution of 30 m, and Sentinel-2 multispectral imagery of 2020 with a spatial resolution of 10 m was used for all the three seasons Rabi, Kharif, and Zaid (2015-2020) to estimate the vegetation cover and chlorophyll content in plant leaves. The results showed 25% area was with good vegetation and high chlorophyll content, and 35% area was under unhealthy vegetation with low chlorophyll content in the Kharif season. In the case of Rabi season, 15% area was under good vegetation and 40% area was under vegetation with low chlorophyll content was recorded. In the Zaid season, 10% area with good vegetation, and 30% area with low vegetation chlorophyll content was estimated. The results indicated that in the arid zone, where primarily low and moderate vegetation cover were recorded contains low and medium chlorophyll content in the plant.